In Silico and In Vitro Approach of Preeclampsia Prophylaxis from Water of Kalianda Kopyor - Fitriana Fitriana; Soetrisno Soetrisno; Sri Sulistyowati; Dono Indarto (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2025)
Preeclampsia (PE) stands as a prominent cause of maternal mortality in developing nations, yet a standardized therapy for PE has not been established. Some pregnant women in Lampung have consumed the water of young kopyor coconut fruit from the Kalianda variety (WKK), although its therapeutic effects remain unexplored. This study aimed to investigate WKK phytochemicals through in vitro and silico analyses. Liquid Chromatography-Mass Spectrometry (LCMS) was employed for phytochemical analysis, while an in silico study involved Autodock, Autodock Tools, Autodock Vina, Biovia Discovery Studio 2020, and Open Babel GUI, alongside pharmacokinetics prediction using the pkCSM strategy. The study assessed the inhibitory potential of WKK on Gentiatibetine and curcumenolacto C, targeting the PE ACE2 receptor (1R24) through molecular docking with the 3D structure. Post-docking analysis, including binding affinities, hydrophobic interactions, and pharmacokinetic predictions, was conducted. WKK exhibited relatively low binding affinities for Gentiatibetine (-4.86 kcal/mol), curcumenolactone C (-2.96 kcal/mol), and aspirin (-5.12 kcal/mol). Multiple hydrophobic interactions were observed, such as Van der Waals, Salt Bridge, Conventional Hydrogen Bond, Alkyl, 162, and Lys 129. The receptor IR displayed a high bond-free energy, like aspirin docked with the same gene receptor. Pharmacokinetics predictions indicated that WKK possesses a favorable profile. In conclusion, WKK phytochemicals demonstrated a notable docking score comparable to aspirin, suggesting its potential for preventive therapy use.